TEKNIK SELF-MANAGEMENT DALAM KONSELING KELOMPOK UNTUK MENINGKATKAN KEMANDIRIAN SOSIAL KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN (PKH) - Syahrepah; Darimis (IKIP Siliwangi, 2026)
Social independence is an important indicator in assessing the success of family empowerment programs, particularly in the Family Hope Program (PKH) through P2K2 group counseling activities. However, most Beneficiary Families (KPM) still show a high level of dependence on government assistance, limited decision-making ability, and low control over their daily socio-economic behavior. This article aims to analyze the effectiveness of self-management techniques in group counseling as an intervention approach to foster independent behavior among KPM. The analysis covers the concept of social independence, the dynamics of group counseling in P2K2, and the relevance of self-management components to behavioral change. The method used is a literature review focusing on group counseling theories, self-management models, PKH implementation guidelines, and empirical findings related to improving social independence. The results show that self-management contributes to increasing social independence through self-control, self-monitoring, self-planning, and self-evaluation. These aspects help participants internalize behavioral changes, set realistic goals, and improve reflective abilities. In addition, group counseling provides social support that strengthens the behavior change process through discussion, experience sharing, and motivational support.